2015
DOI: 10.1088/0004-637x/809/2/141
|View full text |Cite
|
Sign up to set email alerts
|

Constraining Neutrino Cooling Using the Hot White Dwarf Luminosity Function in the Globular Cluster 47 Tucanae

Abstract: We present Hubble Space Telescope observations of the upper part (T eff > 10 4 K) of the white dwarf cooling sequence in the globular cluster 47 Tucanae and measure a luminosity function of hot white dwarfs. Comparison with previous determinations from large scale field surveys indicates that the previously determined plateau at high effective temperatures is likely a selection effect, as no such feature is seen in this sample. Comparison with theoretical models suggests that the current estimates of white dwa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 62 publications
1
45
0
2
Order By: Relevance
“…Our analysis strongly rules out that value, but we also find better fitting hydrogen layers at the thick end of the range usually considered by modelers . The 95% confidence range on f s in Hansen et al (2015, which is equivalent to our parameter n A ) was found to be < < f 0.6 1.7 s , which agrees with what we have found. The differences in these values can be attributed both to the inclusion of additional data in our analysis, and to different statistical assumptions made in fitting the models.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our analysis strongly rules out that value, but we also find better fitting hydrogen layers at the thick end of the range usually considered by modelers . The 95% confidence range on f s in Hansen et al (2015, which is equivalent to our parameter n A ) was found to be < < f 0.6 1.7 s , which agrees with what we have found. The differences in these values can be attributed both to the inclusion of additional data in our analysis, and to different statistical assumptions made in fitting the models.…”
Section: Discussionsupporting
confidence: 91%
“…This data set is described in detail in Section 2. The analysis discussed in this paper complements the work in Hansen et al (2015). In that paper, similar white dwarf cooling models were fit to the ACS data shown as the surrounding annulus in Figure 1.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations